Sibaliparriq Local Wisdom as a Model for Children’s Education in Coastal Families of Polewali Mandar - Awaru, A. Octamaya Tenri; Jumadi, Jumadi; Sadriani, Andi (Universitas Negeri Semarang, 2024)
Sibaliparriq, a local wisdom rooted in Mandar cultural values, is pivotal in shaping children’s character within coastal families in Polewali Mandar. This research explores and analyzes the role of Sibaliparriq as an educational model and identifies the challenges of its implementation. Using a qualitative descriptive approach, data were gathered through observation, interviews, and documentation from 12 coastal families applying Sibaliparriq in child-rearing. The findings show that Sibaliparriq significantly influences child education in several ways: it fosters a harmonious household through cooperation and shared responsibility; helps meet children’s needs, including food, clothing, education, and entertainment; it supports the educational process by guiding parents in teaching essential values and norms; enhances character development, instilling manners, firmness, and gentleness; it aids in imparting religious values; it prepares children to interact respectfully in society; and helps prevent social deviant behavior through proper guidance and role modeling. Challenges include modernization and globalization affecting traditional values, limited resources for Sibaliparriq-based education, and a shift towards formal education over local wisdom.